Survei Literasi Kesehatan Pada Pasien Diabetes Di Puskesmas Kota Yogyakarta: Health Literacy Level in Diabetes Patients at Primary Health Centers (Puskesmas) in Yogyakarta City - Firman; Baharuddin, Nurul Hikmah; Nugroho, Faradilla Esa (Universitas Ahmad Dahlan, 2023)
Background The diabetes/sugar disease phenomenon is caused by changes in people's lifestyles, starting from eating behavior, physical activity habits, unbalanced diets, obesity, and others. This is related to the patient's socio-demographic situation, especially knowledgeor literacyregarding the importanceof health behavior. If literacyislow, it will have an impact on DM patients being limited in taking preventive measures, slow treatment when sick, inefficient use of medicines, high treatment costs, and evenresult in social discrimination. Apart from that, it is also greatly influenced by the support of health providers such as Community Health Centers. Community health centers arehubs forproviding basic services, especiallythoseinvolving educationand health promotion efforts starting from the preparedness of health workers, readiness to collaborate in providing correct health information, and adjusting interaction patterns with patients. This researchaims to identifya picture of the health literacy of DM Puskesmas patients in Yogyakarta City. By considering socio-demographic characteristics, access to information sources, individual health history, and relationship with health providers. Methods: The research design is a cross sectional study. The research was carried out at 3 Community Health Centers in YogyakartaCity. The research subjects were DM patients aged 15-60 years who received treatment at the Community Health Center. The sampling method was carried out using probability, namely purposive sampling. The total number of samples was 45 patients who were undergoing treatment at the Community Health Center. To see the influence of the health literacy level of DM patients on their treatment, univariate analysis, bivariate and multivariate analysis were carried out. Results: The results of the study showed that socio-demographic factors, JKN membership, easy access to health information and health providers did not have a significant influence. Meanwhile, income level and health status factors had an influence on the health literacy level of diabetes patients at the Yogyakarta City Health Center (P,0.05; CI: 95%). Conclusion: Healthcenter providers of health workers need to strengthenearly health promotion and education activities for people who have the potential or symptoms of DM.